2000
DOI: 10.1136/jech.54.9.709
|View full text |Cite
|
Sign up to set email alerts
|

Management of menorrhagia in primary care---impact on referral and hysterectomy: data from the Somerset Morbidity Project

Abstract: Objective-To investigate the management of menorrhagia in primary care and its impact on referral and hysterectomy rates. Design-Prospective observational study. Setting-11 general practices from the Somerset Morbidity Project. Subjects-885 women consulting their general practitioner with menorrhagia over four years. Main outcome measures-Proportions of these women investigated and treated with drugs in primary care, referred to a gynaecologist and undergoing operative procedures. The relation between investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 13 publications
0
30
2
5
Order By: Relevance
“…Within the general population, the prevalence of HMB is difficult to estimate; a recent study of women aged 30e49 years consulting their general practitioner (GP) showed a rate of around 3% presenting with HMB [12]. No reference is made to the body mass index (BMI) of the women within this group.…”
Section: Prevalence Of Menstrual Disorders In Obese Womenmentioning
confidence: 99%
“…Within the general population, the prevalence of HMB is difficult to estimate; a recent study of women aged 30e49 years consulting their general practitioner (GP) showed a rate of around 3% presenting with HMB [12]. No reference is made to the body mass index (BMI) of the women within this group.…”
Section: Prevalence Of Menstrual Disorders In Obese Womenmentioning
confidence: 99%
“…For menorrhagia, the therapy options have recently changed from more conservative medical approaches, with antifibrinolytics and hormones, to replacement therapy (RT) and prophylaxis [2,15,16]. This shift towards a rational, replacement-based approach is likely to change clinical practice that, until recently, frequently adopted surgical approaches including endometrial ablation [17] or hysterectomy [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies in different cultures have associated it with one of the most common causes of regular absenteeism among young women in schools, work places, sports participation, and other public functions (Banikarim et al, 2000;Grant et al, 2000;Walraven et al 2002;El-Gilany et al, 2005). Dysmenorrhoea, a sharp painful menstrual cramp in the lower abdomen and menorrhagia, heavy and prolonged menstrual bleeding (Grant et al, 2000;KamatemesiMugisha et al, 2007) both of menstrual disorder and discomfort are peculiar health problems that have attracted little or no health concern. Such issues are often omitted in the public health agenda of many low and middle income countries.…”
Section: Introductionmentioning
confidence: 99%